2022
DOI: 10.3390/ijms23158485
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of SARS-CoV-2 Vaccines for Short- and Long-Term Immunity: A General Overview for the Pandemic Contrast

Abstract: Background: The recent COVID-19 pandemic produced a significant increase in cases and an emergency state was induced worldwide. The current knowledge about the COVID-19 disease concerning diagnoses, patient tracking, the treatment protocol, and vaccines provides a consistent contribution for the primary prevention of the viral infection and decreasing the severity of the SARS-CoV-2 disease. The aim of the present investigation was to produce a general overview about the current findings for the COVID-19 diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 344 publications
0
6
0
Order By: Relevance
“…Germ-free mice, raised in sterile conditions without exposure to microorganisms, have been used as experimental models to study the impact of germ-free mice on bone density and structure. Microbiota transplantation studies have shown that introducing a diverse and healthy microbiota positively affects bone health in recipients, while transplanting from diseased or imbalanced donors may lead to compromised bone density and structure [20][21][22][23][24]. In human trials, probiotics have been found to modulate the GM, with certain strains associated with increased calcium absorption and improved bone density.…”
Section: Experimental Evidence Of the Impact Of The Gastrointestinal ...mentioning
confidence: 99%
“…Germ-free mice, raised in sterile conditions without exposure to microorganisms, have been used as experimental models to study the impact of germ-free mice on bone density and structure. Microbiota transplantation studies have shown that introducing a diverse and healthy microbiota positively affects bone health in recipients, while transplanting from diseased or imbalanced donors may lead to compromised bone density and structure [20][21][22][23][24]. In human trials, probiotics have been found to modulate the GM, with certain strains associated with increased calcium absorption and improved bone density.…”
Section: Experimental Evidence Of the Impact Of The Gastrointestinal ...mentioning
confidence: 99%
“…However, it does exist in the S protein of SARS-CoV-2, and owing to the cleavage by furin, the S protein binds ACE2 strongly and spreads infection. (ii) Entry: After the S protein binds to the ACE2 receptor, an enzyme called TMPRSS2, a type II transmembrane serine protease, on the cell surface cleaves part of the S protein, altering its binding [ 7 , 40 , 41 ]. This triggers the fusion of the viral envelope with the cell membrane, allowing it to enter the cell.…”
Section: Structural Characterization Of Sars-cov-2mentioning
confidence: 99%
“…The recent COVID-19 pandemic has accelerated the adoption of digital health (eHealth) technologies, paving the way for greater incorporation of these technologies into PC settings [ 49 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. eHealth solutions can facilitate primary healthcare delivery and contribute to the realization of universal health coverage [ 70 , 71 ].…”
Section: Introductionmentioning
confidence: 99%